The role and uses of antibodies in COVID-19 infections: a living review. Issue 1 (28th January 2021) - Scourfield, D Oliver; Reed, Sophie G; Quastel, Max; Alderson, Jennifer; Bart, Valentina M T; Teijeira Crespo, Alicia; Jones, Ruth; Pring, Ellie; Richter, Felix Clemens; ,; Burnell, Stephanie E A
Abstract: Coronavirus disease 2019 has generated a rapidly evolving field of research, with the global scientific community striving for solutions to the current pandemic. Characterizing humoral responses towards SARS-CoV-2, as well as closely related strains, will help determine whether antibodies are central to infection control, and aid the design of therapeutics and vaccine candidates. This review outlines the major aspects of SARS-CoV-2-specific antibody research to date, with a focus on the various prophylactic and therapeutic uses of antibodies to alleviate disease in addition to the potential of cross-reactive therapies and the implications of long-term immunity.